Dukungan Sosial Orang Tua dan Self-Esteem (Penelitian Terhadap Tim Kabupaten Sumedang di Ajang O2SN Jawa Barat) - Anggi Setia Lengkana; Ayi Suherman; Entan Saptani; Rana Gustian Nugraha (Journal of Sport Science and Education, 2020)
This study aims to determine the effect of parental social support on the district team. sumedang in the O2SN elementary school level in West Java. The method used is an associative method with survey design. The research design used is cross-sectional. The instrument used was a questionnaire for Parents' Social Support and the Hare Self-esteem Scale (HSS). The research location is in Sumedang Regency. The population is elementary students who are members of the district team. Sumedang to attend the O2SN West Java Province. The results showed that social support has a great influence on self-esteem. This is evidenced by the significance test of variable X to Y which shows the results of Y = a + b X1 = 222,109 + 0.729 X1 The percentage obtained between X to Y is 0.405 x 100% = 40.5%. Parental social support has a significant influence on self-esteem. This is evidenced by an increase test that shows the value of tcount with ttable, it turns out that tcount = 4.568 is greater than ttable = 1.697, or the value of sig. smaller than the 0.05 significance level that is 0.047, so it can be concluded that the Social Support (X) regression equation against Self esteem (Y) is significant. The conclusion of the research shows that there is a great influence given by the social support of parents on children's self esteem.